Effect of Co on Si and Fe-containing intermetallic compounds (IMCs) in Al–20Si–5Fe alloys - Kilicaslan, M. Fatih; Yilmaz, Fikret; Hong, Soon-Jik; Uzun, Orhan (Elsevier BV, 2012)
Abstract The effects of cobalt addition on microstructure and mechanical properties of Al–20Si–5Fe–XCo (X=0, 1, 3, and 5) alloys were reported in this study. The alloys were produced by both conventional sand casting and melt-spinning at 20 m/s disk velocity. Microstructures of the samples were investigated using X-ray diffractometry (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Vickers micro-hardness tester was used for hardness measurements. Results showed that Co addition can alter morphology of Fe-bearing intermetallic compounds (IMCs) from long rod/needle-like structures to short rod-like ones, and lead to a more homogenous distribution in the microstructure. Addition of 5 wt% Co leads to a decrease in average size of the primary silicon phases in as-cast Al–Si alloys. In melt-spun alloys, with the addition of Co, the microstructure became finer and more homogenously distributed, while thickness of the featureless zone has seen great increase. The optimum Fe to Co ratio was found to be 1 for suppressing the undesirable effect of Fe-bearing acicular/needle-like intermetallic compounds.